Common Complications of Implantable Collamer Lens Implantation - Anshul Garg; Sanjay Chaudhary; Alka Pandey (Delhi Journal of Ophthalmology)
The ever-growing need for refractive correction led to the advent of phakic intraocular lenses, wherein the implantable collamer lens (ICL) is a major boon. The latest model of ICL, the V4c is a relatively safe lens, but a few complications have been reported. In this article, we discuss the various complications reported with the ICL for better knowledge of the surgeons. This will further help in providing in depth information of the factors that should be kept in mind before and after performing the surgery to prevent any unwanted complication.